Implementasi Supervisi Kepala Sekolah dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 di MI Al-Wathoniyah 5 - Mania, Majidah Aqifah; Nugraha, Mulyawan Safwandy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study evaluates the performance of madrasahs in implementing various aspects of education contained in the education unit accreditation instrument. Through interviews and observations, the study analyzed several critical points in school management: the principal's competence in academic supervision, creative and innovative leadership, building harmonious relationships between madrasah members, managing facilities and infrastructure, and managing finances. The results showed several challenges faced by the madrasah in implementing the new curriculum, managing human resources, and developing facilities and infrastructure. The implications of this study highlight the importance of training and coaching for teachers and educators, improving guidance and counseling services for students, and increasing cooperation between madrasahs and related parties to improve the quality of education. By considering these findings, madrasahs can take strategic steps to improve the effectiveness and efficiency of the learning process and create a conducive learning environment for developing students' potential.